Laporan Kasus: Perempuan 19 Tahun dengan Anastomosis Colon Relaparotomy Post Ileus Obstruktif - Muhammad Afifudin Auliy; Catur Widayat (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Anastomotic leaks are one of the most feared complications after bowel surgery, given the potential for devastating consequences. Anastomotic leaks can occur early in the postoperative period and are a major concern for medical personnel, particularly surgeons. A 19-year-old female patient, referred from Bhakti Persada Hospital to the emergency room of Dr. Sayidiman Hospital, Magetan, on July 20, 2024, presented with complaints of vomiting, black stools with blood spots, and epigastric pain radiating to the back. The patient had previously been hospitalized at Bhakti Persada Hospital for 14 days and was diagnosed with obstructive ileus. She subsequently underwent a laparotomy. Postoperatively, the patient's suture site began to discharge a fecal-smelling fluid, indicating a complication of the anastomosis. A relaparotomy was performed to further evaluate the patient's condition. A follow-up examination revealed an anastomotic leak between the jejunum and sigmoid colon. After anastomotic repair, the patient was transferred back to the ward for further care. A few days later, she was discharged home. However, some time after discharge, the patient returned to the emergency room complaining of pain in the surgical wound and a foul-smelling discharge from the wound. The next step was to refer the patient to Dr. Sutomo General Hospital in Surabaya for further treatment, given the complexity of the patient's condition. This incident highlights the importance of being aware of anastomotic complications and prompt treatment to prevent more serious consequences. Complications such as anastomotic leaks require intensive postoperative attention, including careful monitoring for signs of infection or leakage at the suture site. Optimal preventive measures need to be implemented, taking into account both surgical techniques and the preparedness of medical facilities to handle potential complications.